The eventual outcome of patients who had lower limb amputations due to peripheral vascular disease at Pelonomi Hospital, Bloemfontein - C De Klerk; G Du Plessis; J J Fourie; A O'Neill; S J A Smit; G Joubert (South African Family Practice)
Background: Peripheral vascular disease (PVD) presenting with irreversible lower limb pathology has a high morbidity and mortality rate. This study aimed to determine the outcome of patients who underwent lower limb amputations (LLAs) because of PVD at Pelonomi Hospital, Bloemfontein, 2008–2011.